The nutritional value, bioactive availability and functional properties of garlic and its related products during processing - Sunanta, Piyachat; Kontogiorgos, Vassilis; Pankasemsuk, Tanachai; Jantanasakulwong, Kittisak; Rachtanapun, Pornchai; Seesuriyachan, Phisit; Sommano, Sarana Rose (Frontiers in Nutrition, 2023)
Garlic, a common culinary spice, is cultivated and used around the globe. Consumption of garlic and its supplements reduces the risk of diabetes and cardiovascular disease and boosts the immune system with antibacterial, antifungal, anti-ageing, and anti-cancer properties. Diallyl sulphide, diallyl disulfide, triallyl trisulfide, phenolics, flavonoids, and others are the most commercially recognised active ingredients in garlic and its products. In recent years, global demand for medicinal or functional garlic has surged, introducing several products such as garlic oil, aged garlic, black garlic, and inulin into the market. Garlic processing has been demonstrated to directly impact the availability of bioactive ingredients and the functionality of products. Depending on the anticipated functional qualities, it is also recommended that one or a combination of processing techniques be deemed desirable over the others. This work describes the steps involved in processing fresh garlic into products and their physicochemical alterations during processing. Their nutritional, phytochemical, and functional properties are also reviewed. Considering the high demand for functional food, this review has been compiled to provide guidance for food producers on the industrial utilisation and suitability of garlic for new product development.